(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
In this paper, on the basis of the Conventional Figurative Language Theory (Dobrovol’skij and Piirainen 2005), we focus on the symbolic background in the metaphorical use of the figure of orchid, and its traces in the figurative expressions, from a linguo-cultural perspective. First, we present a brief survey of the history of orchid in China and its role in Chinese art; then we analyze semantically and culturally a large number of idioms, figurative expressions, as well as some ancient poems. This study demonstrates the productivity of the orchid, reflecting its particular cultural connotations in the Chinese language. In this way, it provides reference materials which may facilitate learning, teaching and translation of Chinese, as well as intercultural communication. Besides, it also contributes to a better understanding of the interaction between language and culture especially between phraseology and culture.